THE BIOACTIVE CONTENT AND ANTIOXIDANT ACTIVITY OF HONEY BEEHIVES (Apis dorsata BINGHAMI) FROM THE BOGANI NANI WARTABONE BOLAANG MONGONDOW NATIONAL PLANT - Yermia S Mokosuli; Herry Sumampouw; Hendra Pratama Maliangkay; Jimmy Langi (Indonesian Biodiversity Journal, 2021)
Bee Honey (Apis dorsata Binghami) Is a subspecies of A. dorsata which is only found in sulawesidan island and surrounding islands and until now has not been successfully cultivated. Various studies have been conducted species of trees used for nesting places, nesting behavior, biotic conditions, physical surrounding nesting trees and nesting characteristics. This study aims to obtain secondary metabolite components and scientific data of antioxidant activity of honeybee extract (Apis dorsata Binghami) derived from Bogani Nani Wartabone Bolaang Mongondow National Park, North Sulawesi Province. The method of extraction in this research was conducted using maceration with methanol solvent, phytochemical test and antioxidant activity analysis using method (1,1-definil-2-picrilhidrazil) by measuring absorbance absorption at maximum wavelength using UV-Vis spectrophotometer. The results of the phytochemical test show that the honeycomb (Apis dorsata Binghami) contains alkaloids, flavonoids, saponins and tannins. From the analysis results showed that with the increasing concentration of extracts, the greater the antioxidant activity is marked by decreasing the value of IC50. The honeycomb (Apis dorsata Binghami) has IC50 of 212.42 ppm in comparison with vitamin C IC50 of 59.34 ppm